Temporal super-resolution of 2D/3D echocardiography using cubic B-spline interpolation. (April 2020) - Jalali, Mohammad; Behnam, Hamid; Davoodi, Fateme; Shojaeifard, Maryam
Highlights: Increasing frame rate in echocardiography video using cubic B-spline interpolation of intensity variation time curve signals. Interpolation accuracy evaluation of 2D/3D echocardiography and color Doppler videos using cubic B-spline interpolation. Qualitative evaluation of 2D/3D echocardiography and color Doppler videos, showing the results to an expert. Comparing B-spline interpolation of different orders to show superiority of Cubic B-spline for interpolation. Abstract: Echocardiography is an important imaging modality in daily clinical practices. Lack of image quality and limited number of frames per second are the major problems of this modality. Frame rate limitation becomes worse in 3D echocardiography, because it has to scan a volume instead of a plane and acquisition of a volume consumes more time compared to its two-dimensional counterpart. Higher frame rates can help improve medical diagnostics like tracking movements of cardiac valves and position of ventricular endocardial, myocardial and epicardial by tracing the small transient motions in order to better characterize the functionality of cardiac activities. There are a few numbers of temporal super-resolution methods to improve the frame rate. Here, we have proposed a temporal interpolation method using splines. Comparison of the results with that of the state-of-the-art methods shows promising outcomes to enhance echocardiography frame sequences in both two and three-dimensional clinical echocardiography images. Results show that proposed method is doing interpolation more precisely and it also performs about ten times faster in the sense of processing time compared to the latest works to increase the frame rate. We have also shown that interpolation accuracy depends greatly on how many frames per second we have initially and how many frames we want to add to the original sequence. This frame rate increase is also applied to the color Doppler in both 2D and 3D echocardiography and results are presented.